The perfect microsite: How to maximize Posidonia oceanica seedling settlement success for restoration purposes using ecological knowledge. (October 2020) - Alagna, Adriana; Zenone, Arturo; Badalamenti, Fabio
Abstract: The use of sexual propagules to restore seagrass meadows has raised increasing attention in the last years as seed-based strategies avoid impacts on donor beds while preserving genetic diversity in restored populations. However, the availability of suitable microsites for seedling establishment at transplantation locations is crucial in order to achieve positive outcome of restoration actions. In this study we develop ad-hoc holders that act as optimal microsites for Posidonia oceanica seedling establishment. Holders are intended to be transferred in the field for restoration purposes after few months of indoor seedling culture. Seedling ability to self-anchor to rocky substrates via adhesive root hairs was exploited. We tested rocky holders with different designs in order to maximize seedling survival and settlement. The effect of the holder design on seedling anchorage performances was evaluated. Holders were provided with different topographical complexity and substrate slope. Topographical complexity significantly influenced settlement success, as seedlings did not attach to flat holders, while anchorage reached 100% on holders provided with complexity at seed and the root scales. Substrate slope did not affect the percentage of anchored seedlings, conversely it influenced root growth pattern and thus anchorage stability. This study shows how ecological knowledge of species' life history strategies and associated critical traits provides valuable hints to develop alternative approaches to seagrass restoration tailored to the biology of the system under study. Highlights: Posidonia oceanica seedlings were grown on ad-hoc rocky holders with restoration aims. Seedling ability to adhere to consolidated substrates via root hairs was exploited. Holders with different designs where tested to maximize root adhesion to the substrate. Proper substrate topographical complexity and slope allowed to reach 100% anchorage. The unit plant-holder is conceived to be transplanted in the field after adhesion.